'I'm beginning a new life': the (im)possibility of beginning or ending in Larisa Shepit'ko's Wings and Pavel Chukhrai's The Thief. (2nd January 2020) - Lugarić, Danijela
ABSTRACT: This article analyses two films, Larisa Shepit'ko's Wings ( Kryl'ia, 1966) and Pavel Chukhrai's The Thief ( Vor, 1997), from the point of view of the poetics of a traumatic past as the source for the present. Within the theoretical framework of the concepts of trauma, (post)memory and the uncanny, this analysis aims to answer the following questions: after the historical trauma of the Second World War, or the 'Great Patriotic War', is there any sense in talking not only about the future, but also about the present – if what Chris Lorenz terms 'hot history' haunts a person to the extent that it completely shapes his/her life? How does time 'return'? Where is trauma located? What are the meanings of the figures of 'lost objects' in these films? What happens when trauma is anchored around a myth?